Moderna Museet 1998. - Ar, Fyrtio; Elliott, David; Moderna museet, Stockholm (London : Scala Publishers, 1998)
Arbus, Diane ; Bacon, Francis ; Balla, Giacomo ; Beuys, Joseph ; Brancusi, Constantin ; Braque, Georges ; Calder, Alexander ; Chagall, Marc ; De Chirico, Giorgio ; Cornell, Joseph ; Dali, Salvador ; Duchamp, Marcel ; Erixson, Sven ; Ernst, Max ; Fahlström, Öyvind ; Fautrier, Jean ; Giacometti, Alberto ; González, Julio ; Gris, Juan ; Hjorth, Bror ; Jonsson, Sune ; Judd, Donald ; Kandinsky, Wassily ; Kienholz, Edward ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kylberg, Carl ; Laurens, Henri ; Leger, Fernand ; Linnqvist, Hilding ; Lundquist, Evert ; Magritte, René ; Matisse, Henri ; Miro, Joan ; Mondriaan, Piet ; Nilsson, Axel ; Oldenburg, Claes ; Oppenheim, Meret ; Picabia, Francis ; Picasso, Pablo ; Pollock, Jackson ; Rauschenberg, Robert ; Rodhe, Lennart ; Rosenquist, James ; de Saint Phalle, Niki ; Sandberg, Ragnar ; Schwitters, Kurt ; Segal, George ; Sköld, Otte ; Strömholm, Christer ; Tinguely, Jean ; Ultvedt, Per Olof ; Viola, Bill ; Warhol, Andy
Zweeds
boek